The reformation [videorecording]. (Camarillo, CA : Goldhil Entertainment, 2003)
On October 31, 1517, Martin Luther, a Catholic Priest, nailed to the door of Withenberg Cathedral in Germany his "95 Theses" attacking a certain practices of the Roman Catholic Church. When he refused to recant and apologize, the church excommunicated him, and he went into hiding in fear for his life.
Keywords: Church History -- reformation, 1517-1648; Church history -- modern period